Introduction to deep learning using R : a step-by-step guide to learning and implementing deep learning models using R - Beysolow II, Taweh (Apress®, 2017)
The abundance of data and demand for superior products/services have driven the development of advanced computer science techniques, among them image and speech recognition. Introduction to Deep Learning Using R provides a theoretical and practical understanding of the models that perform these tasks by building upon the fundamentals of data science through machine learning and deep learning. This step-by-step guide will help you understand the disciplines so that you can apply the methodology in a variety of contexts. All examples are taught in the R statistical language, allowing students and professionals to implement these techniques using open source tools.
Keywords: Machine learning.; R (Computer program language); Big data.; Programming languages (Electronic computers); elektronické knihy; electronic books